Analysis on implementation of an intestinal and multivisceral transplantation program at Hospital das Clinicas, School of Medicine, University of São Paulo - unique health system by using the PMBOK methodology - David, Andre Ibrahim; Alves, Fabio Luis; D’Albuquerque, Luiz Augusto Carneiro (Brazilian Journal of Transplantation, 2012)
Purpose: To analyze with an established methodology Project Management Body of Knowledge (PMBOK) the implementation of an Intestine Transplant Service at HC-USP, in has a partner project between the National Transplant System (SNT) and NHS. Materials and Methods: Through the methodological analysis tool, the Project Management Body of Knowledge (PMBOK - Table 1) conducted the study in each stage of the Project Implementation (Program), with a critical look on each stage (Integration, Scope, Time, Cost, Quality, Human Resources, Communications, Risk, Procurement and Stakeholders). To analyze if the necessary steps have been performed in the correct way (those already performed) and to identify the areas for improvement in those tasks which have not yet been performed. Group Processes: 1 Initiation 2 Planning 3 Execution 4 Monitoring and Control 5 Closure. Results: The results were analyzed by using the concepts described in the Table. Conclusion: According to the knowledge acquired and the evaluation results of each item with a final note, the analysis has shown that along the process, the working groups in each process and their areas of operation were appropriately correlated, as it was required along the project. Table: According to the PMBOK 5th edition knowledge areas, the analysis has proven that each process and its areas of actuation were adequately correlated along the project.